2017
DOI: 10.1038/srep41577
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the cutworm Spodoptera litura (Lepidoptera: Noctuidae) to two Bt corn hybrids expressing Cry1Ab

Abstract: To examine the responses of the secondary lepidopteran pest Spodoptera litura to two Bacillus thuringiensis (Bt) corn hybrids [5422Bt1 (Event Bt11), 5422CBCL (MON810)] expressing Cry1Ab, larval bioassays with Cry1Ab toxin, corn leaves or kernels and bagging on corn plants were conducted. The results showed that larvae displayed a similar performance when fed kernels, but not leaves of 5422Bt1, 5422CBCL and their near-isogenic non-Bt corn (5422). Significantly higher Cry1Ab amounts were detected in larvae fed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…nubilalis , Yao et al [ 29 ] reported an overexpression of one CAT gene after feeding with Cry1Ab toxin. Furthermore, in another lepidopteran species, Spodoptera litura higher CAT activity was measured when larvae were fed on kernels of two Bt maize hybrids expressing Cry1Ab [ 30 ]. Since many carotenoids can directly scavenge O2 – in the cell [ 31 ], carotenoids can exhibit competitive relations with CAT, neutralizing the H 2 O 2 generated by O2 – dismutation.…”
Section: Discussionmentioning
confidence: 99%
“…nubilalis , Yao et al [ 29 ] reported an overexpression of one CAT gene after feeding with Cry1Ab toxin. Furthermore, in another lepidopteran species, Spodoptera litura higher CAT activity was measured when larvae were fed on kernels of two Bt maize hybrids expressing Cry1Ab [ 30 ]. Since many carotenoids can directly scavenge O2 – in the cell [ 31 ], carotenoids can exhibit competitive relations with CAT, neutralizing the H 2 O 2 generated by O2 – dismutation.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco cutworm, Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae), is a polyphagic pest, widespread throughout South and East Asia, Africa and Oceania [ 15 ]. It feeds on over 389 species of plants [ 16 ], including legumes, cotton, cabbage, cauliflower, castor, peanut, tubers and oilseeds [ 17 ]. In the states of Rajasthan and Maharashtra, India, in 2008–2009 it caused soybean losses of 64 million USD and 300 million USED respectively [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spodoptera litura (Fabricius) commonly known as tobacco cutworm is a serious polyphagous pest and is distributed throughout tropical as well temperate regions of world (Tenywa et al, 2018) It is a serious crop pest of important cash crops, vegetables, fodder, ornamental and horticulture (Ahmad et al, 2013).The larvae feeds on leaves, fresh emerging seedlings, brackets and soft shoots (Yinghua et al, 2017) and causes severe damage with yield loss ranging from 26-100% (Tuan et al, 2014). Farming community largely depends on conventional synthetic insecticides for the management of this pest.…”
Section: Introductionmentioning
confidence: 99%